What do we know about the future of food systems? - Wiebe, Keith D.; Gotor, Elisabetta (International Food Policy Research Institute, 2025)
Food systems have achieved remarkable progress in recent decades, but moving forward, they will face significant challenges in delivering the many outputs and services we expect and need. This book presents a collection of short chapters on the current state of knowledge about different aspects of the future of food systems, written by a diverse group of scientists from around the world with expertise in a wide range of related disciplines and regions.